Optical Depth Measurements of Clouds Using a Mie Scattering LIDAR System - Lagrosas, Nofel; Holdsworth, John; Villarin, S.J., Jose (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
The optical properties of clouds are important factors in studying the global radiation balance. In particular, the optical depth distribution of clouds, which may be drived from the extinction coefficient, is useful in modeling the radiation distribution in the atmosphere (Pal et al., 1992). In the western Pacific tropics, little is known of the optical properties, including optical depth, of clouds despite this region being an extremely active and important one for global moisture transport (Dorado et al., 1998). This paper presents the calculated optical depths of observed clouds at the Atene de Manila University, 14.64N, 121.07E, Manila, Philippines from LIDAR backscattered signals. LIDAR, an acronym for Light Detection And Ranging, is the optical analogue of radar and is used in the field of atmospheric physics primarily for the study of clouds, volcanic particles, aerosols and dust.